Fungicidas minerales (Polisulfuro de calcio + Caldo de ceniza) en el control de moniliasis (Moniliophthora roreri Cif & Par) en cacao (Theobroma cacao L.) variedad “CCN-51” a la edad de tres años - Navia Chanalata, Víctor Hugo (2016)
The effect of mineral Fungicides (calcium Polysulfide + ash Broth to the 3, 4, 5 and 6% respectively) in the control of moniliasis (Moniliophthora roreri Cif & Par.) in of Trinidad cacao was evaluated variety (Theobroma cacao L.) “CCN-51” at the age of three years completely was used a design at random with five treatments (ABSOLUTE WITNESS, PC+CC3%, PC+CC4%, PC+CC5%, PC+CC6%) with five repetitions each treatment. In the observation variable we had the Incidence of the moniliasis in cacao fruits, the quantitative variables were severity and Effectiveness of the Product. In the evaluation of the incidence of the moniliasis (Moniliophthora roreri Cif & Par) in cacao fruits (Theobroma cacao L.) are the results, in which it is observed that during the period of evaluation it highly existed significant statistical differences for the treatments with a probability (P<0.05), is referentially in the last observation that went to the 75 days, that the smaller incidence obtained it (PC+CC to 6%), whereas the 10 greater incidence obtained it (PC+CC to 3%). In the evaluation of the severity of the moniliasis (Moniliophthora roreri Cif & Par) in cacao fruits (Theobroma cacao L.) are the results in which it is observed that during the period of evaluation it highly existed significant statistical differences for the treatments with a probability (P<0.05) is referentially in the last observation that went to the 75 days, that less severe were (PC+CC to 6%), whereas most severe it was (absolute witness). In the evaluation of the effectiveness of the product for the moniliasis (Moniliophthora roreri Cif & Par) in cacao fruits (Theobroma cacao L.) are the results, in which it is observed that during the period of evaluation it highly existed significant statistical differences for the treatments with a probability (P<0.05), is referentially in the last observation that went to the 75 days, that most effective were (PC+CC to 6%), whereas less effective it was (PC+CC to 3%). In the evaluation of the production in cacao fruits (Theobroma cacao L.) are the results in which it is observed that during the period of evaluation it highly existed significant statistical differences for the treatments with a probability (P<0.05) is referenced in the last observation that went to the 75 days, that the best weight was obtained in (PC+CC to 6%), whereas the one of less weight obtained it (Absolute Witness). According to the economic analysis of the production of cacao (Theobroma cacao L.) through course of the investigation, we could determine that (PC+CC to 6%) he was the one that obtained the best benefit cost by quintal, whereas the smaller benefit was obtained in (Absolute Witness) by quintal of dry weight.